Legal texts and legal issues : proceedings of the second Meeting of the International Organization for Qumran Studies, Cambridge, 1995 : published in honour of Joseph M. Baumgarten - Baumgarten, Joseph M.; Bernstein, Moshe J.; García Martínez, Florentino.; Kampen, John. (Studies on the Texts of the Desert of Judah, 1997)
This volume contains the papers presented to the second meeting of the International Organization for Qumran Studies, held in Cambridge (UK) in 1995. The papers, all dealing with the theme of the meeting, Legal Texts and Legal Issues , are arranged into five sections. The first section, 'New Texts', contains publications of legal texts, including a copy of the Temple Scroll from Cave 4. Section two presents studies on different aspects of 4QMMT, from its use of Scripture to its concept of Holiness and its relevance for understanding the history of Qumran. The following two sections contain studies on legal texts and legal issues, such as purity, divorce, and sabbath legislation. The final section, 'Qumran and the New Testament', focuses on the importance of the Qumran texts for the study of the New Testament. The volume is published in honour of Joseph M. Baumgarten, and it contains an appreciation of Baumgarten's work, as well as his bibliography.